Targeted and stimuli–responsive mesoporous silica nanoparticles for drug delivery and theranostic use. Issue 12 (19th August 2019) - Aquib, Md; Farooq, Muhammad A.; Banerjee, Parikshit; Akhtar, Fahad; Filli, Mensura S.; Boakye‐Yiadom, Kofi O.; Kesse, Samuel; Raza, Faisal; Maviah, Mily B. J.; Mavlyanova, Rukhshona; Wang, Bo
Abstract: For cancer therapy, the usefulness of mesoporous silica nanoparticles (MPSNPs) has been widely discussed, likely due to its inorganic nature and excellent structural features. The MPSNPs‐based chemotherapeutics have been promisingly delivered to their target sites that help to minimize side effects and improve therapeutic effectiveness. A wide array of studies have been conducted to functionalize drug‐loaded MPSNPs using targeting ligands and stimuli‐sensitive substances. In addition, anticancer drugs have been precisely delivered to their target sites using MPSNPs, which respond to multi‐stimuli. Furthermore, MPSNPs have been extensively tested for their safety and compatibility. The toxicity level of MPSNPs is substantially lower as compared to that of colloidal silica; however, in oxidative stress, they exhibit cytotoxic features. The biocompatibility of MPSNPs can be improved by modifying their surfaces. This article describes the production procedures, functionalization, and applications of biocompatible MPSNPs in drug delivery. Abstract :